Best Practice at Your Fingertips: The WISHeS School Nurse Procedure Website - DuChateau, Teresa A. (NASN Sch Nurse, 2015)
School nurses are responsible for providing and supervising school nursing services for children with complex health concerns. Given school nurses frequently practice in isolation and may have limited access to clinical practice changes, they can benefit from up-to-date, evidence-based resources. Additionally, the resources must account for the fact that the nursing procedures will be performed in the unique setting of a school building and in many cases, will be performed by school personnel who have limited formal education in health care. This article provides an overview of a newly developed, easy to use, online school nursing procedures website for school nurses and other school personnel.